2021
DOI: 10.1007/s11845-021-02662-8
|View full text |Cite
|
Sign up to set email alerts
|

Infants infected with SARS-CoV-2 and newborns born to mother diagnosed with COVID-19: clinical experience

Abstract: Background Almost every day, new information about the COVID-19 pandemic continues to emerge. COVID-19 presents a mild clinical picture in children. However, how it goes in newborns and pregnant is still entirely unclear. Aims To present the clinical course of SARS-CoV-2 positive newborns and outcomes of babies born to mothers diagnosed with COVID-19. Methods The present cohort-study examined two groups. The first group includes fourteen newb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The study by Norman et al showed that <5% of neonates born to COVID-19 mothers had NEC, of which perinatal asphyxia occurred in 2% [24]. Another study showed that no NEC was found in neonates born to COVID-19 mothers in which the neonates had good Apgar scores [19] A study conducted by Yaman et al who showed that feeding intolerance is a common clinical symptom in neonates with COVID, which these gastrointestinal symptoms are associated with premature infants [25]. The severity of the COVID-19-positive pregnant woman is related to the condition of the newborn being born.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Norman et al showed that <5% of neonates born to COVID-19 mothers had NEC, of which perinatal asphyxia occurred in 2% [24]. Another study showed that no NEC was found in neonates born to COVID-19 mothers in which the neonates had good Apgar scores [19] A study conducted by Yaman et al who showed that feeding intolerance is a common clinical symptom in neonates with COVID, which these gastrointestinal symptoms are associated with premature infants [25]. The severity of the COVID-19-positive pregnant woman is related to the condition of the newborn being born.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, respiratory symptoms were evaluated in 22 studies (26,28,33,34,38,39,(45)(46)(47)(48)(49)(50)(51)(52)54,55,57,58,62,64,65,67), and the proportion of these was 23% (95% CI: 18-29%, I 2 =81%, P<0.01, Figure S1A). Nasal symptoms were evaluated in 17 studies (27,28,33,38,39,45,47,48,(52)(53)(54)(55)58,62,63,65,67), S2B).…”
Section: Proportion Of Clinical Symptomsmentioning
confidence: 99%
“…Rashes were evaluated in 8 studies (28,33,38,52,54,58,62,65), and the proportion of this symptom was 4% (95% CI: 2-6%, I 2 =63%, P<0.01, Figure S2C). Feeding difficulty was evaluated in 19 studies (26,28,33,38,39,48,49,(51)(52)(53)(54)(55)58,59,62,63,(65)(66)(67), and the proportion of this symptom was 20% (95% CI: 14-26%, I 2 =89%, P<0.01, Figure S2D). Results of subgroup analyses were provided in Table 2.…”
Section: Proportion Of Clinical Symptomsmentioning
confidence: 99%
“…Many studies have found that most newborns infected after birth have gastrointestinal or respiratory symptoms ( 20 ). Yaman et al observed some infected newborns and found that the most common symptoms were feeding intolerance, cough, elevated fever, and respiratory distress ( 21 ). It may also occur as a rare case of multisystem inflammatory syndrome in children in newborns due to COVID-19—presenting with stage 11 b necrotizing enterocolitis ( 22 ).…”
Section: Introductionmentioning
confidence: 99%